Problematyka „spraw zdrowia” w dziełach polskich klasyków pedagogiki społecznej – Heleny Radlińskiej, Aleksandra Kamińskiego, Ryszarda Wroczyńskiego - Syrek, Ewa (Pedagogika Społeczna Nova, 2021)
The article presents views on “health matters” contained in the works of the classics of social peda- gogy: Helena Radlińska, Aleksander Kamiński, and Ryszard Wroczyński to emphasize their topicality concerning the contexts of contemporary health pedagogy and health education